1994
DOI: 10.1086/133347
|View full text |Cite
|
Sign up to set email alerts
|

KSPEC-a near-infrared cross-dispersed spectrograph

Abstract: KSPEC (Af-band spectrograph) is an infrared spectrograph designed primarily for spectroscopy in the 2.0-2.5 fim region. It offers two different optical configurations. The first is a cross-dispersed echelle mode designed to cover the atmospheric windows from 1-2.5 fim in one spectral frame of a 256x256 format on a NICMOS-3 HgCdTe detector array. This configuration of the spectrograph provides medium spectral resolution (A/AA~500) for spectral classification work, emission-line detection, and redshift measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…The spectrum of this well-studied young, low-excitation PN was previously shown to be dominated by lines of H I and He I in the near-IR, with a hot dust continuum (Willner et al 1979;Zhang & Kwok 1992;Hodapp et al 1994). Hora et al (1993) and Paper I showed broad-and narrowband near-IR images of the PN, showing the elliptical, double-lobed structure in the IR.…”
Section: Ic 418mentioning
confidence: 83%
“…The spectrum of this well-studied young, low-excitation PN was previously shown to be dominated by lines of H I and He I in the near-IR, with a hot dust continuum (Willner et al 1979;Zhang & Kwok 1992;Hodapp et al 1994). Hora et al (1993) and Paper I showed broad-and narrowband near-IR images of the PN, showing the elliptical, double-lobed structure in the IR.…”
Section: Ic 418mentioning
confidence: 83%
“…First, we used currently proven technologies to minimize the need for and cost of research and development. For example, at the time of NIRIMÏs design phase, the NICMOS3 arrays, developed by Rockwell International Science Center, had been proven in other astronomical cameras (e.g., Hodapp, Rayner, & Irwin 1992 ;Hodapp et al 1994 ; Thompson et al 1994 ;Nadeau et al 1994). Second, we kept the engineering of the design to a minimum.…”
Section: Introductionmentioning
confidence: 99%
“…1). Originally a near-infrared cross-dispersed grating spectrometer, 9 KSPEC was repurposed for ultra-low noise detector characterization for the JWST Packaging and Manufacturing Technology program, where the background was shown to be at the level of a few photons/pixel/hour for 5 µm cutoff material.…”
Section: Saphiramentioning
confidence: 99%